INTELLIGENT MULTI-COLOURED LIGHTING SYSTEM DESIGN WITH FUZZY LOGIC CONTROLLER - Mutua, Paul W.; Mbuthia, Mwangi (APTIKOM Publisher, 2016)
This paper describes the design of an intelligent energy efficient lighting system that uses multi-colouredLEDs and a fuzzy logic controller to produce light of the required luminance level and colour in a typical roomspace. The lighting system incorporates automatic control of a room?s window shade opening, convenientlyharvesting daylight. Appropriate room occupancy sensors were set to dim off the LEDs if there are no people in theroom. A movement sensor was also considered for dimming the LEDs if the persons in the room are asleep. A colourdecoder was included in the control system, to determine the LEDs? output light colour and dim them off if the colourrequirement is not selected. The colour decoder also closes the window shade if required light colour is not white.Two Fuzzy Logic controllers were used in the system; one to control opening of the room?s window shade viamicrocontroller, and the other to control the LEDs? output luminance. The study was limited to simulation of thedesign in a MATLAB software environment using Fuzzy Logic Toolbox and Simulink blocks. The simulation testresults confirmed that the LEDs? output luminance decreases as the amount of daylight entering the room increases.The designed system intelligently saves lighting electrical energy while maintaining the room?s comfortableillumination levels and colour requirements.